2013
DOI: 10.1002/mrd.22192
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of legumain and cystatin 6 expression at the maternal-fetal interface in pigs

Abstract: Cathepsins (CTSs), a family of lysosomal cysteine proteases, and their inhibitors, cystatins (CSTs), play a critical role in endometrial and placental tissue remodeling during the establishment and maintenance of pregnancy in many species including rodents, sheep, cow, and pigs. In this study, we determined expression of legumain (LGMN), a cathepsinmember, and its inhibitor, CST6, at the maternal-fetal interface in pigs. Expression of both LGMN and CST6 mRNAs increased during mid- to late pregnancy in the uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Interestingly, the genes LGMN and CTSB, which play important roles in the endosomal processing of endocytosed antigens, were down-regulated. The LGMN gene encodes a cysteine protease that presents bacterial and endogenous peptides to major histocompatibility complex (MHC) class II molecules in the lysosomal and endosomal systems [ 39 ]. The CTSB protein is a lysosomal cysteine proteinase that is comprised of a dimer of disulfide-linked heavy and light chains that are made from the same protein precursor that is involved in proteolytic processing [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the genes LGMN and CTSB, which play important roles in the endosomal processing of endocytosed antigens, were down-regulated. The LGMN gene encodes a cysteine protease that presents bacterial and endogenous peptides to major histocompatibility complex (MHC) class II molecules in the lysosomal and endosomal systems [ 39 ]. The CTSB protein is a lysosomal cysteine proteinase that is comprised of a dimer of disulfide-linked heavy and light chains that are made from the same protein precursor that is involved in proteolytic processing [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CTSs and CSTs in the uterine endometrium has been shown in many species including rodents, humans, ruminants and pigs [ 50 52 ], and it has been suggested that CTSs and CSTs play important roles in endometrial remodeling in the uterine endometrium during the reproductive cycle and pregnancy [ 52 ]. In pigs, CTSB, CTSL1, and LGMN are expressed by endometrial luminal epithelial and chorionic epithelial cells at the maternal-conceptus interface during pregnancy and endometrial expression of CTSB and CTSL1 is induced by progesterone [ 51 , 53 ], suggesting that their action is required to remodel uterine endometrial and placental tissues and facilitate transplacental transport of nutrients. CST6 is expressed in the uterine endometrium during the estrous cycle and in pregnancy, and also in the chorionic epithelia of the placental membrane with increasing levels during late pregnancy [ 53 ], suggesting that cell type-specific expression and function of CST6 is critical in regulation of CTS action for appropriate maternal-fetal interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin L1 (CTSL1) was localized to chorionic epithelia that form areolae, which absorb secretions from uterine glands. Message for the cysteine endopeptidase LGMN and its inhibitor CST6 localized with strong intensity in both the luminal epithelium (LE) and glandular epithelium (GE) as well as in the chorionic epithelium by day 30 of pregnancy in pigs (Shim et al, 2013). In SCNT pregnancies, both LGMN and CST6 were misregulated in the endometrium underlying the placenta compared to IVV pregnancies.…”
Section: Discussionmentioning
confidence: 99%